Factors affecting the delay in management of cases in the emergency department, National University Hospital, Kuala Lumpur, 1999 - Nor Azian Abdul Wahab; Khalib Abd. Latip (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
A cross-sectional study using qualitative and quantitative method was carried out in the Emergency Department at the National University Hospital, Kuala Lumpur between 1 st to 26th J une 1999, to study the factors that affect the delay in the management of cases in the Emergency Department. Qualitative method involving in-depth interviews with different categories of staff of the Emergency Department was used to find out problems faced by them in the management of patients and also to study predisposing factors in the management that may lead to delay. Quantitative method was carried out using semistructured questionnaire on patients and a time-keeping form attached with each questionnaire to note the total length of stay and times spent by patients at different stations in the Emergency Department. The time spent was traced retrospectively at the end of the survey, in order to determine any delays in the management of cases. Results of quantitative survey showed that the majority of delayed cases was seen in triage 2 patients (71%) compared to 42% delay in triage 3 and 35% delay in triage 4 (p<0.001). Patients who attended the Emergency Department on a working day are more likely to be delayed (49.6%) compared to 23% delay in patients who came on a holiday (p<0.001). Patients who came to the department during office hours were much more delayed (55.6%), compared to 33.5% delay in those who came after office hours (p<0.001). Patients who were subjected to diagnostic investigations were significantly more delayed compared to those not needing investigations. Patients who were admitted were significantly more delayed compared to those allowed to go home. Patients referred to specialists were also found to be significantly more delayed than those not referred to specialists. Qualitative survey revealed the problem of lack of staff to manage cases, inappropriate utilisation by non-emergency cases due to the absence of an outpatient department in the hospital and communication problem between doctors and patients due to the employment of foreign doctors.